Aplikasi Game Petualangan Pengenalan Budaya Tradisional Sulawesi Selatan - Aidi Faiz; Wahyuddin Wahyuddin; A. Irmayani Pawelloi (Jurnal Sintaks Logika, 2025)
In today's digital era, children's interest in games is very high, but often games only provide entertainment without educational value. This research aims to create an adventure game that integrates elements of South Sulawesi culture into gameplay that can provide an interactive and useful learning experience. Experimental research methods using Unity and Blender and visual studio code, which was implemented in the laboratory of the University of Muhammadiyah Parepare. The results of creating an adventure game application can integrate elements of South Sulawesi culture, such as traditional weapons, traditional clothing, and traditional food. These games can enhance children's understanding of the local culture while providing an engaging and educational gaming experience and making a contribution that blends entertainment with cultural education.